Kontrafaktik der Gegenwart - Navratil, Michael (Gegenwartsliteratur, 2021)
Non-realistic narratives are currently immensely popular but have been frequently accused of political escapism. This study models counterfactuality using theories of fiction and shows the great affinity that this narrative technique shares with political writing. Analyses of works by Christian Kracht, Kathrin Röggla, Juli Zeh, and Leif Randt demonstrate the diversity and relevance of political variations on reality in contemporary literature.